TAHAPAN KOTA BANDUNG MENUJU KOTA KREATIF - , Aris Puji Sunarso, Prof. Ir. Achmad Djunaedi, MUP., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The idea of creative city was firstly raised by Charles Landry in 1991 in a study entitled âThe Creative City and Its Cultural Economyâ. The idea of creative city is emerging as an alternative answer to the increasingly complex problems facing cities in the world today, such as urbanization, congestion, and socioeconomic problems. The creative city was firstly applied in the cities in the United Kingdom starting in 1996 and then spread to the developed countries in Europe and America in the early 2000s. In developing countries, particularly in Indonesia has only been few cities are applying creative city strategy into its development strategy, and Bandung City is a pioneer of the application of creative city in Indonesia. This study aims to: (1) Formulate the stages of the process toward creative city of Bandung, (2) Revealing the actors that play a role in the process of developing Bandung as a creative city, and (3) Revealing the factors that may influence the development process as a creative city of Bandung. This study used a qualitative approach with the case study method. The data and information collected by means of semi-structured interviews, observations and review of documents and literature. In this way research, data analysis using time series analysis techniques and pattern matching. This study took locus in Bandung City because Bandung City is the pioneer of creative cities in Indonesia and in 2007 was named as a pilot project of creative cities throughout East Asia. Results from this study is that the process toward creative city of Bandung has 4 stages which began development of the creative economy, the process of network formation, strengthening the potential of networking, and the improvement of public spaces. In summary, the process starts from economic dimension, then social dimension, dimension of cultural and environmental dimensions. The actors that play a role in the development of the city of Bandung towards creative city are community, government, universities, private sector and the media. The factors that influence is a factor of leadership, communication, external inspiration, bureaucratic structures and community participation.